Adult Equivalence Scales, Inequality and Poverty in New Zealand - John Creedy; Catherine Sleeman (New Zealand Government, The Treasury, 2004)
This paper examines the sensitivity of inequality and poverty measures to the choice of adult equivalence scales and the type of income unit examined. Comparisons are made using parametric equivalence scales, and income units include individuals, equivalent adults and households. The results are based on HES data for total expenditure. A variety of equivalence scales, for New Zealand, Australia, the UK and the OECD are examined. The implications of varying the poverty line are also considered.
Keywords: D31; D63; H23; I31; I32; 330; Inequality; poverty; equivalence scales; living standard; income unit